Novelties in Costa Rican Stelis (Orchidaceae: Pleurothallidinae): two new species and a new record in the "Dracontia group" - Karremans Lok, Adam Philip (2017)
Stelis dies-natalis and Stelis aenigma, belonging to a group of mostly Middle American species alternatively placed in genus Dracontia, are described and illustrated based on living material. They were both found in oak forests at high elevations on diverse peaks of the Talamanca mountain range in Costa Rica. The first, S. dies-natalis, was found on Cerro Buena Vista and Cerro Urán, and is somewhat similar to S. hydrabut can be distinguished by the relatively short inflorescence, the dark purple flowers with a yellow lip covered by dark purple warts, the apiculate apex of the petals and the lip with a shortly acuminate apicule. The second, S. aenigma, was initially believed to be a specimen of S. dies-natalis when it was collected on Cerro Utyum, but itcan be easily distinguished by the few-flowered inflorescence that barely exceeds the leaf, the reddish flowers, the sigmoid lip and the cucullate, obtuse anther.Stelis platystylis, a species previously known from Mexico to Nicaragua is illustrated based on living material from Costa Rica.